Social Network Analysis: K-Pop Fans' Social Action as Digital Solidarity via Twitter - Astuti Sri Pawening (Eduvest - Journal of Universal Studies, 2023)
This research aims to explore the social actions of K-Pop fans as a form of digital solidarity through Twitter. In contrast to the research of Marinescu & Balica (2013), Pramadya & Oktaviani (2016), Yoon (2018), this study tries to map explore social networks by analyzing actors who play a role in social action as digital solidarity of BTS K-Pop fans, namely ARMYs through Twitter and looking at the related relationships between actors. The research method used is using Social Network Analysis using Netlytic and Gephi software with data sourced from tweets on Twitter accounts. The results of this study explain the social network of actors involved in the social action of BTS fans, namely ARMY with donation activities as a form of digital solidarity through four aspects, namely commons, assemblies, swarms and weak networks.